1994
DOI: 10.1172/jci116971
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces prostaglandin H synthase-2 protein and mRNA in human alveolar macrophages and blood monocytes.

Abstract: We and others have previously demonstrated that human alveolar macrophages produce more PGE2 in response to lipopolysaccharide (LPS) than do blood monocytes. We hypothesized that this observation was due to a greater increase in prostaglandin H synthase-2 (PGHS-2) enzyme mass in the macrophage compared to the monocyte. To evaluate this hypothesis, alveolar macrophages and blood monocytes were obtained from healthy nonsmoking volunteers. The cells were cultured in the presence of 0 to 10 ,g/ml LPS. LPS induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
186
1
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(204 citation statements)
references
References 45 publications
14
186
1
3
Order By: Relevance
“…Upon stimulation with endotoxin these cells produce a variety of cytokines, lipid mediators and radicals. Recent studies have indicated that endotoxin enhances the expression of inducible cyclooxygenase-2 (Cox-2) [2][3][4][5][6], which results in the increased formation of prostanoids by Kupffer cells and other macrophages [3,[7][8][9]. Interestingly, lipopolysaccharide (LPS)-induced prostaglandin E2, D2 and thromboxane B2 formation and Cox-2 expression are stimulated up to 10-fold when ambient osmolarity increases from 300 to 350 mosmol/1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Upon stimulation with endotoxin these cells produce a variety of cytokines, lipid mediators and radicals. Recent studies have indicated that endotoxin enhances the expression of inducible cyclooxygenase-2 (Cox-2) [2][3][4][5][6], which results in the increased formation of prostanoids by Kupffer cells and other macrophages [3,[7][8][9]. Interestingly, lipopolysaccharide (LPS)-induced prostaglandin E2, D2 and thromboxane B2 formation and Cox-2 expression are stimulated up to 10-fold when ambient osmolarity increases from 300 to 350 mosmol/1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of COX-2 expression requires de novo mRNA and protein synthesis (21), indicating regulation at the transcriptional level. The promoter region of human COX-2 gene has been cloned and sequenced, and shown to contain putative recognition sequences for a variety of transcriptional factors, including NF-B, NF-IL-6, and cAMP response element (22).…”
mentioning
confidence: 99%
“…In contrast, the COX-2 isoform is undetectable in most tissues under basal conditions, but marked transcriptional activation can be observed in macrophages and other cell types by the endotoxin lipopolysaccharide (LPS) and proinflammatory cytokines. [1][2][3] Interestingly, systemic inflammatory insults cause a robust transcriptional activation of COX-2 along cells of the mouse and rat microvasculature, although the intensity of the signal and the pattern of expression depend on the challenge and the dose of the inflammatory agents. [4][5][6][7][8] Intravenous (i.v.)…”
mentioning
confidence: 99%